Multifunctional carbon dot for lifetime thermal sensing, nucleolus imaging and antialgal activity. Issue 36 (24th August 2018) - Li, Hao; Zhang, Mengling; Song, Yuxiang; Wang, Huibo; Liu, Chang'an; Fu, Yijun; Huang, Hui; Liu, Yang; Kang, Zhenhui
Abstract : The electrochemical synthesis of multifunctional carbon dots, that are used for a fluorescence-based nanothermometers, nucleolus probe and antialgal agents. Abstract : Multifunctional carbon dots (CDs) with lifetime thermal sensing, nucleolus imaging, and antialgal activity properties were synthesized directly from ascorbic acid aqueous solution by a one-step electrochemical method at room temperature. The as-prepared CDs are responsive to temperature and exhibit an accurate linear response of fluorescence intensity vs. temperature (20–100 °C). These CDs can enter a cell and nucleolus, adsorb on the nucleic acids (DNA and RNA) and the fluorescence intensity of CDs is increased by the adsorption of nucleic acids. In addition, the CDs can inhibit the activity of RuBisCO in Anabaena sp., leading to reducing the growth of Anabaena sp. All these properties make the CDs serve as effective fluorescence-based nanothermometers, nucleolus probes, and antialgal agents.